FXR controls the tumor suppressor NDRG2 and FXR agonists reduce liver tumor growth and metastasis in an orthotopic mouse xenograft model. - Ulrich Deuschle; Julia Schüler; Andreas Schulz; Thomas Schlüter; Olaf Kinzel; Ulrich Abel; Claus Kremoser (PLoS ONE, 2012)
The farnesoid X receptor (FXR) is expressed predominantly in tissues exposed to high levels of bile acids and controls bile acid and lipid homeostasis. FXR(-/-) mice develop hepatocellular carcinoma (HCC) and show an increased prevalence for intestinal malignancies, suggesting a role of FXR as a tumor suppressor in enterohepatic tissues. The N-myc downstream-regulated gene 2 (NDRG2) has been recognized as a tumor suppressor gene, which is downregulated in human hepatocellular carcinoma, colorectal carcinoma and many other malignancies.We show reduced NDRG2 mRNA in livers of FXR(-/-) mice compared to wild type mice and both, FXR and NDRG2 mRNAs, are reduced in human HCC compared to normal liver. Gene reporter assays and Chromatin Immunoprecipitation data support that FXR directly controls NDRG2 transcription via IR1-type element(s) identified in the first introns of the human, mouse and rat NDRG2 genes. NDRG2 mRNA was induced by non-steroidal FXR agonists in livers of mice and the magnitude of induction of NDRG2 mRNA in three different human hepatoma cell lines was increased when ectopically expressing human FXR. Growth and metastasis of SK-Hep-1 cells was strongly reduced by non-steroidal FXR agonists in an orthotopic liver xenograft tumor model. Ectopic expression of FXR in SK-Hep1 cells reduced tumor growth and metastasis potential of corresponding cells and increased the anti-tumor efficacy of FXR agonists, which may be partly mediated via increased NDRG2 expression. FXR agonists may show a potential in the prevention and/or treatment of human hepatocellular carcinoma, a devastating malignancy with increasing prevalence and limited therapeutic options.